2020
DOI: 10.1097/dcc.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Situation, Background, Assessment, and Recommendation Handover Tool in Improving Communication and Satisfaction Among Jordanian Nurses Working in Intensive Care Units

Abstract: Background The SBAR (situation, background, assessment, and recommendation) is a standardized handover tool that has been utilized in health care settings. It has positive impacts on staff communication and patient quality of care. In Jordan, few reports are available about handover tools' impacts. Purpose To evaluate the implementation of the SBAR among nurses in intensive care units (ICUs) in Jordan. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
2
11
0
5
Order By: Relevance
“…SBAR effectiveness was examine using the 43-item ICU physician-nurse questionnaire, which included subscales for general relationship and communication, teamwork and leadership, and job satisfaction. The finding indicate that there was a significant improvement in posttest knowledge scores [13] . (Jiang et al 2020) stated their study that conduct in hospital in Guangzhou research subjects were 100 clinical nurses.…”
Section: Discussion Overall Nurses Knowledge and Difference Regarding Communication Strategy (Sbar) At The Pre-test And Post-test Period mentioning
confidence: 81%
See 1 more Smart Citation
“…SBAR effectiveness was examine using the 43-item ICU physician-nurse questionnaire, which included subscales for general relationship and communication, teamwork and leadership, and job satisfaction. The finding indicate that there was a significant improvement in posttest knowledge scores [13] . (Jiang et al 2020) stated their study that conduct in hospital in Guangzhou research subjects were 100 clinical nurses.…”
Section: Discussion Overall Nurses Knowledge and Difference Regarding Communication Strategy (Sbar) At The Pre-test And Post-test Period mentioning
confidence: 81%
“…The effectiveness of program was clear improved the practical knowledge of nurses regarding communication strategy which of their level was moderate at pretest then improved to high level and the result revealed that were high statistically significant differences between the pre-test and the post-test at (p<0.05). (Dalky et al 2020) conducted a quasi-experimental approach with a pretest-posttest was adopted. 71 ICU nurses took part in the study as a convenience sample.…”
Section: Discussion Overall Nurses Knowledge and Difference Regarding Communication Strategy (Sbar) At The Pre-test And Post-test Period mentioning
confidence: 99%
“…The result of the study conducted by Abela et al showed that the structure of handover procedures and the use of the SBAR tool can improve the impact of handover and staff satisfaction. Satisfaction regarding the information received during handover increased from 34% to 41% (19). In the result of the study conducted by Fabila et al, recipients' perception about the new handover protocol indicated improvement in information adequacy and clearness, decrease errors, and lesser inconsistencies in the patient described in the new procedure (18,19).…”
Section: Discussionmentioning
confidence: 97%
“…Handover is a communication process among nurses that involves conveying patient information and is important in ensuring quality and continuity of nursing care [1,2]. Accurate and comprehensive handover helps nurses sufficiently understand patient needs and increases the stability and efficacy of nursing; it also has a positive impact on nurses' job satisfaction and enhancing their expertise [3]. Accurate handovers help reduce errors and enable nurses who lack clinical experience to improve by receiving suggestions from advanced nurses [4].…”
Section: Introductionmentioning
confidence: 99%